A comparison study of InGaN/GaN multiple quantum wells grown on (111) silicon and (0001) sapphire substrates under identical conditions. (3rd November 2022) - Zhu, C; Xu, C; Feng, P; Chen, X; de Arriba, G M; Bai, J; Wang, T
Abstract: Due to an increasing demand of developing III-nitride optoelectronics on silicon substrates, it is necessary to compare the growth and optical properties of III-nitride optoelectronics such as InGaN based light emitting diodes (LEDs) on silicon substrates and widely used sapphire substrates. GaN-on-silicon suffers from tensile strain, while GaN-on-sapphire exhibits compressive strain. This paper presents a comparative study of InGaN/GaN multiple quantum wells (MQWs) grown on a silicon substrate and a sapphire substrate under identical conditions. It has been found that GaN strain status has a significant influence on the growth and the optical properties of InGaN/GaN MQWs. Photoluminescence measurements indicate the InGaN/GaN MQWs grown on a silicon substrate exhibit significantly longer wavelength emission than those on a sapphire substrate. Detailed x-ray diffraction measurements including reciprocal space mapping measurements confirm that both indium content and growth rate in the InGaN MQWs on the silicon substrate are enhanced due to the tensile strain of the GaN underneath compared with those on the sapphire substrate. This work also presents an investigation on strain evolution during the InGaN MQWs growth on the two different kinds of substrates. A qualitative study based on in-situ curvature measurements indicates that a strain change on the silicon substrate is much more sensitive to a growth temperature change than that on the sapphire substrate. It is worth highlighting that the results provide useful guidance for optimising growth conditions for III-nitrides optoelectronics on silicon substrates.